From West to East : Estimating External Spillovers to Australia and New Zealand - Sun, Yan. (Washington, D.C. : International Monetary Fund, 2011)
This paper examines the size and source of external spillovers to Australia and New Zealand based on a structural vector autoregression (VAR) approach. It finds that during the last decade shocks from emerging Asia have become more important than those from the United States in affecting Australia's business cycle. A 1 percent shock to emerging Asia's growth is found to shift Australian growth by about 1/3 percent. Furthermore, there is evidence that commodity prices dominate the transmission of shocks from emerging Asia to Australia. The influence of emerging Asia on New Zealand is found to come indirectly through Australia, with Australian shocks transmitting almost "one-on-one" to New Zealand, largely through financial factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet